2014
DOI: 10.1186/1471-244x-14-42
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of assertive community treatment for elderly patients with severe mental illness: a randomized controlled trial

Abstract: BackgroundDue to fragmented mental, somatic, and social healthcare services, it can be hard to engage into care older patients with severe mental illness (SMI). In adult mental health care, assertive community treatment (ACT) is an organizational model of care for treating patients with SMI who are difficult to engage. So far all outcome studies of assertive community treatment have been conducted in adults.MethodsIn a randomized controlled trial design we compared the effectiveness of ACT for elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
1
30
0
2
Order By: Relevance
“…Results from the preliminary evaluation have important clinical and service delivery implications. The current study found that most clients treated with the CAIR program remained treated in the community, supporting previous research highlighting that the intensive recovery program promotes person-centered care, encourages collaborative treatment, and reduces the negative consequences associated with admitting older adult clients to a psychiatric hospital (Burns et al, 2007;Pratt et al, 2008;Stobbe et al, 2014). Maintaining clients' connections to their family, carers, and community empowers them to remain in a familiar/ local environment and has the potential to reduce stigma of mental illness (Miller & Brewerton, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results from the preliminary evaluation have important clinical and service delivery implications. The current study found that most clients treated with the CAIR program remained treated in the community, supporting previous research highlighting that the intensive recovery program promotes person-centered care, encourages collaborative treatment, and reduces the negative consequences associated with admitting older adult clients to a psychiatric hospital (Burns et al, 2007;Pratt et al, 2008;Stobbe et al, 2014). Maintaining clients' connections to their family, carers, and community empowers them to remain in a familiar/ local environment and has the potential to reduce stigma of mental illness (Miller & Brewerton, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…settings because inpatient psychiatric beds are often less accessible (Miller & Brewerton, 2009). Although increasing research has been devoted toward implementing and testing this intensive model of psychiatric care (Pratt, Van Citters, Mueser, & Bartel, 2008;Stobbe et al, 2014;Wilberforce et al, 2011), few studies have investigated the effectiveness of a Community Aged Intensive Recovery (CAIR) program for acutely unwell older adults residing in rural or remote settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The three studies which met the inclusion criteria were published in 1996, 2010 and 2014 respectively. One study was carried out in the Netherlands [23], one in Austria [22] and one in Great Britain [21]. All of them were randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 However, the evidence for innovative mental health care strategies for elderly people is scarce. 27 Most studies using ACT, [28][29][30] HT, [31][32][33][34][35] or CRT [36][37][38] did not specifically report whether the innovative care models reduced AHLS in geriatric populations with mental health care needs. A British study showed that CRT and HT significantly reduced admissions of elderly mentally ill patients, but there was no significant difference in AHLS as compared before and after the introduction of these services.…”
Section: Procedures In Medicine Of the World Health Organization Calledmentioning
confidence: 99%